Management integrity, internal control, and organizational culture as accounting fraud predictors - Sri Hartini; Daniel Yusuf; Khairunnida; Siti Asyraini (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to ascertain whether management integrity, internal control, and organizational culture affect accounting fraud separately or all at once. This study used a quantitative associative research methodology. 150 employees of the Medan City BPPRD made up the study's sample population. This study used a purposive sampling method with a sample size of 100 participants. Multiple linear regression analysis is the data analysis method used, and simultaneous and partial tests are used to assess the hypothesis. The research's findings indicate that management integrity, internal control, and organizational culture all have a partial impact on accounting fraud. Management integrity, internal control, and organizational culture all have an impact on accounting fraud.